Core Tax Administration System from the Perspective of the Theory of Planned Behavior - Mutammimah; Pamungkas, Supan; Mayangsari, Sekar (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The adoption of digital tax administration systems is crucial for enhancing tax compliance and administrative efficiency. Understanding the factors that influence taxpayers’ intentions and actual usage is essential for effective implementation. This study aims to examine how attitudes, perceived social norms, and perceived behavioral control affect taxpayers’ intentions to use digital tax systems, and how these intentions, along with perceived behavioral control, impact actual usage. A quantitative approach was employed, using a survey to collect data from 200 taxpayers who actively use the system. The data were analyzed using structural equation modeling with partial least squares. Results show that attitudes, social norms, and perceived behavioral control significantly shape taxpayers’ intentions, while both intention and perceived behavioral control positively influence actual system usage. These findings support the applicability of the theory of planned behavior in understanding the adoption of digital tax systems. The study offers practical insights for tax authorities to enhance system uptake by promoting positive attitudes, supportive social expectations, and stronger perceptions of control among users.